2008
DOI: 10.1118/1.2961611
|View full text |Cite
|
Sign up to set email alerts
|

SU‐GG‐J‐61: Correcting For Missing Data In 4D‐MVCT

Abstract: Purpose: A technique has been developed to retrospectively sort helical tomotherapy sinogram detector data based on the respiration phase. It is not possible to obtain complete sinograms for multiple respiration phases without delivering excessive imaging doses. As such, the sinogram detector data for each respiration phase will be missing projection data necessary to reconstruct an image. The purpose of this study was to develop and test a technique for replacing these missing projections. Method and Material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Zhang et al 73 suggested a new 4D tomotherapy technique that utilises dynamic 4DCT data for treatment plan optimisation. In addition, 4D MVCT data can be acquired and sorted on the basis of respiration phase which allows offline review of target motion 74, 75…”
Section: Recent Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al 73 suggested a new 4D tomotherapy technique that utilises dynamic 4DCT data for treatment plan optimisation. In addition, 4D MVCT data can be acquired and sorted on the basis of respiration phase which allows offline review of target motion 74, 75…”
Section: Recent Developmentmentioning
confidence: 99%
“…In addition, 4D MVCT data can be acquired and sorted on the basis of respiration phase which allows offline review of target motion. 74,75 Real-time tracking of tumour motion and position using IGRT system also become a popular topic, as it allows monitoring of unpredictable infra-fractional organ movement like prostate motion. Such monitoring technique is beneficial to prolonged hypofractionated treatments where high dose per fraction is prescribed.…”
Section: D and Fluoroscopic Imaging With Igrt Systemmentioning
confidence: 99%